Estimation of outcrossing rates in intraspecific (Oryza sativa) and interspecific (Oryza sativa × Oryza glaberrima) rice under field conditions using agro-morphological markers - Bah, S.; Merwe, R. van der; Labuschagne, Maryke T. (Springer, 2017)
Rice is mainly a self-pollinating crop, but some outcrossing has been reported. Outcrossing with an undesirable donor would lead to the creation of segregants or off-types, which would adversely affect genetic purity and uniformity of the crop. Outcrossing rates in rice under field conditions were investigated using cultivar WAB96-1-1 as a pollen donor and WAB56-104, NERICA 2, NERICA 4 and NERICA 7 as pollen recipients. Levels of outcrossing were investigated up to 30 m from the pollen donor. Dominant morphological markers of red kernel colour and pubescent leaves of the donor were used to identify hybrids. A total of 721 134 plants were investigated. There was an average outcrossing rate of 0.7 ± 0.51%, with a potential outcrossing rate of 2.45 ± 0.86%. Outcrossing rates decreased with increase in distance. It ranged from 2.45% at 0.2 m from the donor to 0.05% at 25 m from the donor. Differences were observed between genotypes and seasons. In season 1 the highest average outcrossing rate of 1.2 ± 0.63% was with WAB56-104 and in season 2 it was 1.1 ± 0.69% with NERICA 4. Outcrossing occurred up to 30 m from the donor. This has implications for germplasm management and conservation and the production of high quality seed. Spatial isolation remains the most practical method to prevent undesirable gene flow. The study indicated that red kernel colour and leaf pubescence can be used to effectively assess outcrossing under field conditions in rice.